ORLANDI, Eni P. (org.) Discurso fundador. Campinas: Pontes, 1993,171 p. - Brandão, Cibele (Cadernos de Linguagem e Sociedade, 2010)
ORLANDI, Eni P. (org.) Discurso fundador. Campinas: Pontes, 1993,171 p.